Serum glucose, urea nitrogen, cholesterol, and total proteins in crossbred repeat breeder and normally cyclic cows - Barson, Rashed Khan; Padder, Shasthi; Md Sayam, Abu Sadath; Rahman, Mohammad Moshiur; Bhuiyan, Mohammad Musharraf Uddin; Bhattacharjee, Jayonta (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study was designed to determine and compare the serum glucose, urea nitrogen, cholesterol, and total protein (TP) level in crossbred repeat breeder (RB) and normally cyclic cows to find out the relationship of these metabolic factors with repeat breeding syndrome (RBS). Materials and Methods: A total of 592 breedable cows from 34 farms were examined from Mymensingh and Chittagong districts. Seventy cows were identified as RB cows and another 10 cows were randomly selected as normally cyclic control cows for this study. Blood sample from each cow was collected and the serum was separated. The serum samples were analyzed by auto blood analyzer. Results: Cows affected with RBS had significant variation in their glucose, urea, and cholesterol levels. Serum glucose (43.00 gm/dl) level was significantly lower than in normally cyclic cows. On the other hand, serum urea and cholesterol levels were significantly higher than in normally cyclic cows. However, the TP concentrations did not differ between RB and cyclic cows. RB cows had a lower trend (6.815 mg/dl) of serum TP than in normally cyclic cows. Conclusion: This research might help scientists and veterinarians to understand that the high serum urea and cholesterol level along with low glucose and TP level could have some effect in the development of RBS in crossbred cows. It will potentially help veterinary practitioners and farmers to take preventive measures against RBS of crossbred cows. J. Adv. Vet. Anim. Res., 6(1): 82-85, March 2019